PENGARUH MANAJEMEN TENAGA PENDIDIK TERHADAP HASIL BELAJAR PESERTA DIDIK DI MTS NEGERI 2 KOTA TASIKMALAYA - Silda, Silda; Nurhikmah, Silda (Program Studi Manajemen Pendidikan Islam, 2025)
Student learning outcomes are influenced by various factors, one of which is teacher management, which plays an important role in creating an effective and high-quality learning process. MTs Negeri 2 Kota Tasikmalaya was chosen as the research location because this school is one of the state madrasahs that plays a strategic role in improving the quality of student learning outcomes, and demonstrates a phenomenon relevant to the topic under study, namely teacher management. This study aims to analyze the extent of the influence of teacher management on student learning outcomes at MTs Negeri 2 Kota Tasikmalaya. The research method used is quantitative correlational with data collection techniques in the form of questionnaires and valid and reliable documentation studies. The research population consists of 55 teachers and 64 students. The teacher sample was taken saturately, while 55 students were selected using the Slovin formula to ensure representativeness. Data were analyzed using IBM SPSS version 26 Windows through validity, reliability, determination coefficient, and t-test to test the hypothesis. Descriptive analysis results at MTs Negeri 2 Kota Tasikmalaya showed that the level of teacher management tendency was in the moderate category with an average of 61.8%. Meanwhile, student learning outcomes were also dominated by the moderate category with an average of 65.5%. The t-test yielded a t-value of 5.023 > t-table 1.674 and significance of 0.000, indicating a significant effect. The R2 value of 0.323 indicates that teacher management influences 32.3% of student learning outcomes at MTs Negeri 2 Kota Tasikmalaya, while the remaining 67.7% is influenced by factors outside the research variables. The significance level of the t-test (0.000 < 0.05) indicates that the effect is statistically significant. This finding reinforces the importance of optimizing teacher management in efforts to improve students' academic achievements comprehensively